Ryanodine receptor dysfunction causes senescence and fibrosis in Duchenne dilated cardiomyopathy - Souidi, Monia (2024)
Background: Duchenne muscular dystrophy (DMD) is an X-linked disorder characterized by progressive muscle weakness due to the absence of functional dystrophin. DMD patients also develop dilated cardiomyopathy (DCM). We have previously shown that DMD (mdx) mice and a canine DMD model (GRMD) exhibit abnormal intracellular calcium (Ca2+) cycling related to early-stage pathological remodelling of the ryanodine receptor intracellular calcium release channel (RyR2) on the sarcoplasmic reticulum (SR) contributing to age-dependent DCM.Methods: Here, we used hiPSC-CMs from DMD patients selected by Speckle-tracking echocardiography and canine DMD cardiac biopsies to assess key early-stage Duchenne DCM features.Results: Dystrophin deficiency was associated with RyR2 remodelling and SR Ca2+ leak (RyR2 Po of 0.03 ± 0.01 for HC vs. 0.16 ± 0.01 for DMD, P < 0.01), which led to early-stage defects including senescence. We observed higher levels of senescence markers including p15 (2.03 ± 0.75 for HC vs. 13.67 ± 5.49 for DMD, P < 0.05) and p16 (1.86 ± 0.83 for HC vs. 10.71 ± 3.00 for DMD, P < 0.01) in DMD hiPSC-CMs and in the canine DMD model. The fibrosis was increased in DMD hiPSC-CMs. We observed cardiac hypocontractility in DMD hiPSC-CMs. Stabilizing RyR2 pharmacologically by S107 prevented most of these pathological features, including the rescue of the contraction amplitude (1.65 ± 0.06 μm for DMD vs. 2.26 ± 0.08 μm for DMD + S107, P < 0.01). These data were confirmed by proteomic analyses, in particular ECM remodelling and fibrosis.Conclusions: We identified key cellular damages that are established earlier than cardiac clinical pathology in DMD patients, with major perturbation of the cardiac ECC. Our results demonstrated that cardiac fibrosis and premature senescence are induced by RyR2 mediated SR Ca2+ leak in DMD cardiomyocytes. We revealed that RyR2 is an early biomarker of DMD-associated cardiac damages in DMD patients. The progressive and later DCM onset could be linked with the RyR2-mediated increased fibrosis and premature senescence, eventually causing cell death and further cardiac fibrosis in a vicious cycle leading to further hypocontractility as a major feature of DCM. The present study provides a novel understanding of the pathophysiological mechanisms of the DMD-induced DCM. By targeting RyR2 channels, it provides a potential pharmacological treatment.